IMPLEMENTASI PERATURAN DAERAH KABUPATEN TUBAN NOMOR 12 TAHUN 2012 TENTANG ORGANISASI DAN TATA KERJA LEMBAGA LAIN DALAM PELAYANAN PERIZINAN DI KABUPATEN TUBAN - Chotimah, Khusnul (Universitas 17 Agustus 1945 Surabaya, 2016)
Tuban District Regulation No. 12 of 2012 is the legal basis for the establishment of BPPT Tuban. BPPT Tuban formation as a commitment Tuban regency government in the improvement of public services, especially in service licensing. The purpose of this study is to describe and analyze the implementation of Tuban District Regulation No. 12 of 2012 licensing service in Tuban and to identify the factors supporting and hindering the implementation of Tuban District Regulation No. 12 of 2012 licensing service in Tuban.This research is a qualitative descriptive study, conducted at BPPT Tuban informant BPPT employees Tuban, using qualitative data analysis techniques with the steps of data reduction, data display and conclusion.The results showed that the implementation of Tuban District Regulation No. 12 of 2012 licensing service has been running well, but not optimal. This is due to a decline in the target duration of the licensing process in 2015 that the target 5,23 is reached only 4,3. The factors supporting the implementation of this policy is the existence of socialization permits, the availability of adequate facilities and infrastructure, support from the government of Tuban and has full authority in the signing of 23 licenses. Whereas the inhibiting factor is the existing human resources is not adequate, there is no incentive for implementing the policy, as well as the unavailability of websites and online information systems.Suggestions from this research is to improve the quality of employees BPPT Tuban through training activities, incentives and sustainable increase in the number of employees, especially with expertise in the field of IT, the need for incentives for employees BPPT Tuban, to avoid the presence of extortion and need the availability of websites and systems information online so that the mechanism of the licensing process can be covered more easily by the public.Keywords: Implementation, Policy, Licensing Service